Diagnóstico e avaliação do sistema público de combate a incêndio na área urbana do município de Passo Fundo - Rintzel, Rodrigo (2021)
Fires are accidental phenomena, unpredictable, but highly preventable. This dissertation presents an overview of the occurrences of fire in buildings in the urban area of Passo Fundo, in the period from 2004 to 2015. Both the terminology of the fire episodes and the severity of the occurrences follow the pattern of registration and cataloging of the database of the Seventh Battalion of the Military Fire Department of Passo Fundo. Based on the importance of a public firefighting system as one of the basic infrastructure networks that should serve an essentially urban, densified and verticalized society such as Passo Fundo, this research project seeks to diagnose and evaluate the public firefighting system in the urban area of the city. The proposed diagnosis and analysis involve access to information and data from the 7th Command of the Fire Department of Passo Fundo, regarding the number of fire occurrences in the urban area, showing the history of fire occurrences, crossing these data with the urban maps of the Integrated Development Master Plan, enabling the identification of areas with higher and lower history of fire occurrences, investigating the relationship between the construction typology, human concentration and urban characteristics of the city. It is expected to contribute with scientific parameters that help in the understanding of the consolidated reality and serve as a subsidy for future decision-making related to public firefighting infrastructure.